Effect of Economic and Demographic Factors on Educational Mismatch Probability of Sectoral Workers - Yunisvita Yunisvita; Muhammad Teguh; Deassy Apriani; Imelda Imelda (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2021)
This paper analyzes effect of economic and demographic factors on probability of overeducated workers in Southern Sumatra. Research using binary logistic regression model to estimate probability of overeducation workers. The data used came from the National Labor Force Survey (SAKERNAS) 2018. Unit of analysis is the workers in Southern Sumatra, including South Sumatra Province, Jambi, Bengkulu, Lampung and Bangka Belitung. Sample consisted of 13 683 workers. Estimation results show that income, sector or business field, age and area of residence affect probability of workers being overeducated. Income is the most dominant factor determining probability by providing a positive effect, but vice versa with age factor. Changes in area of residencefrom rural to urban areas give greater possibility of overeducation but this is not the case if there is a change in employment sector from primary to non-primary.The phenomenon of overeducation implies that workers can more easily adapt and understand their work so that productivity is more easily increased.The possibility of over-education mismatch in the regional labor market in South Sumatra is very unique because although the absorption of workers is still dominated by the primary sector, when there is a change of work to the primary sector, the possibility of overeducation actually decreases.